Manajemen Sekolah Berbasis Mutu - EE Junaidi Sastradiharja (Institut PTIQ Jakarta, 2019)
Quality school is the dream of all parties. High-quality schools are characterized by the management of professional schools, learning activities that run in an innovative, creative and fun way, and can achieve the curriculum targets and optimal absorption, then the learning outcomes show good quality. Quality management of educational resources, especially human resources, curriculum, educational and financial facilities and infrastructure is the most decisive factor in the realization of quality schools. Therefore, managerial capabilities of organizers and school managers largely determine the diversity of school quality. Modern societies term the diversity of school quality as “elite school” which means large, luxurious, and quality or the term “school alit” means small, simple, and lacking in quality. However, what really distinguishes school quality lies in the ability of school administrators and managers to manage or manage the school. Small schools that are professionally managed with quality based, the results will be large and quality schools.